Sun-Earth connection: Boundary layer waves and auroras - Lakhina, G. S.; Tsurutani, B. T.; Arballo, J. K.; Galvan, C. (My University, 2000)
Boundary layers are the sites where energy and momentum are exchanged between two distinct plasmas. Boundary layers occurring in space plasmas can support a wide spectrum of plasma waves spanning a frequency range of a few mHz to 100 kHz and beyond. The main characteristics of the broadband plasma waves (with frequencies > 1 Hz) observed in the magnetopause, polar cap, and plasma sheet boundary layers are described. The rapid pitch angle scattering of energetic particles via cyclotron resonant interactions with the waves can provide sufficient precipitated energy flux to the ionosphere to create the diffused auroral oval. The broadband plasma waves may also play an important role in the processes of local heating/acceleration of the boundary layer plasma.
Keywords: Wave-particle interactions; Boundary layer waves; Aurora